Impact of snow accumulation on CryoSat‐2 range retrievals over Arctic sea ice: An observational approach with buoy data. Issue 11 (8th June 2015) - Ricker, Robert; Hendricks, Stefan; Perovich, Donald K.; Helm, Veit; Gerdes, Rüdiger
Abstract: Radar altimetry measurements of the current satellite mission CryoSat‐2 show an increase of Arctic sea ice thickness in autumn 2013, compared to previous years but also related to March 2013. Such an increase over the melting season seems unlikely and needs to be investigated. Recent studies show that the influence of the snow cover is not negligible and can highly affect the CryoSat‐2 range retrievals if it is assumed that the main scattering horizon is given by the snow‐ice interface. Our analysis of Arctic ice mass balance buoy records and coincident CryoSat‐2 data between 2012 and 2014 adds observational evidence to these findings. Linear trends of snow and ice freeboard measurements from buoys and nearby CryoSat‐2 freeboard retrievals are calculated during accumulation events. We find a positive correlation between buoy snow freeboard and CryoSat‐2 freeboard estimates, revealing that early snow accumulation might have caused a bias in CryoSat‐2 sea ice thickness in autumn 2013. Key Points: CryoSat‐2 range measurements correlate with buoy‐measured snow depth changes Assuming that CryoSat senses the ice freeboard is not justified for thick snow Arctic wide snow depth data are required